Preparation and properties of rubber nanocomposites based on natural rubber/ ethylene propylene diene monomer reinforced with nanosilica, carbon black and barium sulfate - Tran Huu Quang,; Trung Sy, Do; Tien Dung, Nguyen; Huu Huy, Tran; Thi Diep, Nguyen; Quynh Trang, Pham; Cong Nguyen, Pham; Do Quang Khang, (Vietnam Journal of Science and Technology, 2022)
In this work, rubber nanocomposites based on natural rubber/ethylene propylene diene monomer (NR/EPDM) blends and reinforced with nanosilica (NS) in combination with carbon black (CB) and barium sulfate (BS) were prepared by melt blending method in a Brabender internal mixer. The appropriate contents of NS and CB for reinforcing the rubber nanocomposites based on NR/EPDM are 10 and 30 phr (parts per hundred rubber), respectively. The NR/EPDM nanocomposites material reinforced with 10 phr NS and 30 phr CB has the best mechanical properties that with the enhancement of tensile strength over 117% and 40 % compared to that of the NR/EPDM nanocomposite material unreinforced and reinforced with only 10 phr NS, respectively. The appropriate content of BS for replacement of CB in the NR/EPDM blend is 6 phr. The rubber nanocomposite based on NR/EPDM (60/40) blend reinforced with 10 phr NS, 24 phr CB and 6 phr BS has a tight structure, high mechanical properties, and especially, high alkali resistance and heat resistance, abrasion resistance and low endogenous heat due to rotation and friction. This material may be used to manufacture technical rubber products that require heat resistance and stability in alkaline environments, such as conveyor belts used in the cement industry.